Active sampling of volatile chemicals for non-invasive classification of chicken eggs by sex early in incubation - Borras, Eva; Wang, Ying; Shah, Priyanka; Bellido, Kevin; Hamera, Katherine L.; Arlen, Robert A.; McCartney, Mitchell M.; Portillo, Kristy; Zhou, Huaijun; Davis, Cristina E.; Turpen, Thomas H. (PLOS ONE, 2023)
According to industry estimates, approximately 7 billion day-old male chicks are disposed of annually worldwide because they are not of use to the layer industry. A practical process to identify the sex of the egg early in incubation without penetrating the egg would improve animal welfare, reduce food waste and mitigate environmental impact. We implemented a moderate vacuum pressure system through commercial egg-handling suction cups to collect volatile organic compounds (VOCs). Three separate experiments were set up to determine optimal conditions to collect eggs VOCs to discriminate male from female embryos. Optimal extraction time (2 min), storage conditions (short period of incubation during egg storage (SPIDES) at days 8–10 of incubation), and sampling temperature (37.5°C) were determined. Our VOC-based method could correctly differentiate male from female embryos with more than 80% accuracy. These specifications are compatible with the design of specialized automation equipment capable of high-throughput, in-ovo sexing based on chemical sensor microchips.